Food and Health: Science and Technology - Birch, G. G. author. aut Link
XII, 532 p. 19 illus.
Keywords: The Control and Standardisation of National Food Quality. There must be very many different opinions as to what this title means. To some people it will mean the control by legislation of additive and contaminant levels in food, to others it may mean the laying down of compositional standards for different food commodities, yet again some may consider that it covers the nutritional quality of the food and the maintenance of an adequate satisfactory diet for the population of the country. I think certainly that it could be all of these things and a glance at the variety of titles of papers which other speakers will be giving later in this symposium illustrates the very wide area which is covered by food quality in its many aspects. I will try only to present to you some of those aspects which are the concern of government in the control of food quality. I will not concern myself with those aspects which are the concern only of the manufacturer and his customer, and here I am thinking of flavour, appearance and physical state, such as whether canned, fresh or frozen. These aspects, which affect the type of products to be marketed, and also the aspects of quality control which set out to maintain the standard that the manufacturer has set himself, are I think outside my province.